Characteristics of people receiving wound care at home versus in a clinic. Issue 4 (August 2021) - Ogrin, Rajna; Parker, Christina N; Finlayson, Kathleen J; Anderson, Jacinta; Edwards, Helen E
Abstract: Objective: Chronic venous leg ulcers are a common health problem, particularly in older people. Addressing an evidence gap, this article compares the characteristics and healing outcomes of people with venous leg ulcers receiving care in specialist wound clinics with those receiving wound care at home by community home nurses. Methods: A secondary analysis of data was conducted from participants enrolled in a prospective study to develop and validate a risk assessment tool for delayed healing of venous leg ulcers. Descriptive statistics and associations between variables of interest were examined. Categorical variables were analysed using Chi-square and Fisher's exact tests, continuous variables were analysed using t -tests and Mann–Whitney U tests. Significance was set at P < 0.05. Results: Participants from community home nursing ( n = 98, mean age 78.25 ± 10.93) had more risk factors that reduced likelihood of healing their wounds within 24 weeks compared to participants attending wound clinics ( n  = 98, mean age 64.31 ± 15.15). Despite this, the two participant groups healed a similar proportion of wounds (71% clinic versus 66% home nursing) within 24 weeks. Conclusion: Structured, evidence-based care provided in the home by well-trained nurses can achieve venous leg ulcer healing in complex people at rates comparable to specialist clinics.